PEMILIHAN METODE LOT SIZING TERBAIK PADA SISTEM PENDUKUNG KEPUTUSAN PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA UD. TANJUNG SARI PROBOLINGGO - Arief Sandi Destianto; Januar Wibowo; Endra Rahmawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
UD. Tanjung Sari is a coffee bean processing business and caffee shop, established since August 4, 2018 which is located on Jl. Dr. Wahidin No. 80 Sukabumi Village, Mayangan District, Probolinggo City, East Java Province. UD. Tanjung Sari produces processed coffee with 7 varieties, namely: Robusta Argopuro Pulp Natural, Robusta Silo Honely, Robusta Silo Natural, Robusta Silo Anaerobic, Arabica Ijen Wash, Arabica Ijen Natural, and Arabica Ijen Anaerobic. This variety has differences in the type of coffee and the treatment during the processing into Finished Goods. Based on the existing problems, then UD. Tanjung Sari needs a decision support system application by comparing 4 methods, namely: Economic Order Quantity, Lot For Lot, Period Order Quantity, and Silver Meal to get the smallest Total Inventory Cost (TIC). From the test results of the application, it can be concluded that the application is in accordance with the expected functions and needs. The results of application testing can show that the application runs well and is easy to use by users.